Aerogels-Inspired based Photo and Electrocatalyst for Water Splitting to Produce Hydrogen. (December 2022) - Al-Hamamre, Zayed; Karimzadeh, Zahra; Ji, Seulgi; Choi, Heechae; Maleki, Hajar
Abstract: Hydrogen fuel has been considered a sustainable, green, and alternative energy source to fossil fuels for future energy supply. Electro- and photochemical water splitting systems are reported as simple, pollutant-free, low-cost, highly efficient techniques for hydrogel production in large quantities and with high purity. As featured by high porosity, self-supportability, and large surface area, aerogels-based catalysts meet all the required criteria for efficient electro and photocatalysts design for water splitting. Besides the traditional sol-gel technique, today, aerogel synthesis and processing have advanced significantly, mainly because of the emergence of various molecular precursors and low dimensional noble, non-noble metals, and carbon-based building blocks, which require the implementation of different network formation strategies. This versatility in the synthesis and fabrication approaches combined with the unique highly 3D porous microstructural feature enhances the aerogel performance for targeted catalytic reactions with improved efficiencies. Herein, an all-embracing overview of the design and processing aspects of aerogel and aerogel-inspired-based materials with various building blocks is given to provide an insight into their electro- and photo-catalysts performance for the water-splitting process and hydrogen production. We also review the recent theoretical studies based on density functional theory (DFT) for unfolding the mechanism and physics of catalytic reactions on the studied aerogel-based materials. Considering their bright prospects, aerogel-based catalysts can pave the way for the advancement of new high-performance binder-free and free-standing electro-and photo-catalytic materials for water-splitting techniques and, ultimately, the production of green hydrogen, a fuel of the future. Graphical abstract: Image, graphical abstract